DEVELOPING SHORT EDUCATIONAL VIDEO ANIMATION FOR INTENSIVE LISTENING MATERIAL - Maulidias, Riezki Kurniawan; Ikhsanudin, Ikhsanudin; Arifin, Zainal (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research developt short educational video animation for intensive listening material: development research on the eighth grade students of SMP LKIA Pontianak. A goodlistening material is important in listening process. This research purpose of doing thisresearch was to develop a good listening material for students and a teacher?s guide forteacher guidance. The researcher used ADDIE model in this research, but the researcheronly focused on analyze, design, development, and implementation. The analyze phaseinvolved analyzing the curriculum and syllabus used in the SMP LKIA Pontianak fordesign phase. The design phase involved creating storyline, script, and design concept forteacher?s guide for development phase. The development phase involved developinganimation video based on the storyline and script and the teacher?s guide based on previousphase. The implementation phase involved trying out the material to the students, gettingthe feedback, and fixing some errors. Getting the feedback helped the researcher to knowsome problems in the animation video and the researcher used these feedbacks to fix itlater. Finally, from all of those stages the researcher completed L.A.U animation videosalong with the teacher?s guide.Keyword: developing, animation video, listening material, ADDIE